2016
DOI: 10.4037/ccn2016561
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine-Impregnated Dressings and Prevention of Catheter-Associated Bloodstream Infections in a Pediatric Intensive Care Unit

Abstract: Background Bloodstream infections related to use of catheters are associated with increased morbidity and mortality rates, prolonged hospital lengths of stay, and increased medical costs. oBjectives To compare the effectiveness of chlorhexidine-impregnated dressings with that of standard dressings in preventing catheter-related bloodstream infections. Methods A total of 100 children were randomly divided into 2 groups of 50 each: a chlorhexidine group and a standard group. Patient care was provided in accordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 15 publications
4
50
3
6
Order By: Relevance
“…The length of hospital stay, the duration of catheterization, and that of mechanical ventilation were shorter in the former than in the latter group; thus, the reduced CRBSI rate in the CHG-dressing group was considered to be clinically relevant. 13 Although we found no significant between-group difference in the CRBSI rate, no CRBSI caused by a Gram-positive microorganism was noted in the CHG-dressing group.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The length of hospital stay, the duration of catheterization, and that of mechanical ventilation were shorter in the former than in the latter group; thus, the reduced CRBSI rate in the CHG-dressing group was considered to be clinically relevant. 13 Although we found no significant between-group difference in the CRBSI rate, no CRBSI caused by a Gram-positive microorganism was noted in the CHG-dressing group.…”
Section: Discussioncontrasting
confidence: 59%
“…Camins et al 12 studying hemodialysis patients with tunneled central venous catheters, found that the CRBSI rate was reduced when CHG dressings were applied. In pediatric patients undergoing central venous catheterization, Düzkaya et al 13 found that the CRBSI rate was lower in a CHG-dressing group than in a standard-dressing group but, again, statistical significance was not attained. The length of hospital stay, the duration of catheterization, and that of mechanical ventilation were shorter in the former than in the latter group; thus, the reduced CRBSI rate in the CHG-dressing group was considered to be clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled estimates from RCTs are consistent with lower rates of catheter colonization with chlorhexidine sponge dressings compared with standard polyurethane (Category A1-B evidence) 90,[133][134][135][136][137][138] but equivocal for catheter-related bloodstream infection (Category A1-E evidence). 90,[133][134][135][136][137][138][139][140] An RCT reports a higher frequency of severe localized contact dermatitis in neonates with chlorhexidine-impregnated dressings compared with povidone-iodine-impregnated dressings (Category A3-H evidence) 133 ; findings concerning dermatitis from RCTs in adults are equivocal (Category A2-E evidence). 90,134,136,137,141 Survey Findings.…”
Section: Insertion Site Dressingsmentioning
confidence: 82%
“…The majority of local reactions were observed in neonates [35], and serious necrotic lesions were reported in very low birthweight (< 1500 g) preterm neonates [255]. Some trials [253,254] showed a tendency towards lower central line-associated bloodstream infection or local infection rates with chlorhexidine-impregnated dressings. However, these decreased rates never reached the statistical significance [35,[253][254][255][256][257].…”
Section: No Recommendationmentioning
confidence: 99%